Analisis Penerapan Gamifikasi Pada Model Blended Learning Terhadap Hasil Pembelajaran Desain Grafis Studi Kasus : SMK Negeri 10 Malang - Hawim Mahfudah; Satrio Hadi Wijoyo; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
This study was used to determine the results, effects and differences of the application of gamification in the blended learning model to the learning outcomes of Basic Graphic Design with a case study of SMK Negeri 10 Malang. The population was based on the research, namely students of class X in the field of expertise of MM with the sample taken, namely two classes, X MM-1 and X MM-4, which amounted to 15 students each. The two classes were given different labels, namely X MM-4 as the experimental class which was given different treatment, and X MM-1 as the control class which was given learning as usual. The data were taken using pretest and posttest instruments which were then analyzed using the T test. The results of the data analysis were the application of gamification in the blended learning model to the learning outcomes of Basic Graphic Design, which increased in value but did not significantly affect it. This is because the t-count value of the experimental class is 1.911 smaller than the t-table value of 2.14479 for an error level of 5%, while in the control class the t-count value of 2.347 is greater than the t-table value of 2.14479. Based on the results of the t test obtained, the control class and the experimental class experienced an increase in value, but not significantly in the experimental class. In contrast to the control class, the scores obtained by students have increased significantly.